2020
DOI: 10.1007/s40263-020-00722-8
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluation of Vaccines to Treat Opioid Use Disorders: How Close are We to a Clinically Viable Therapeutic?

Abstract: The ongoing opioid crisis, now into its second decade, represents a global public health challenge. Moreover, the opioid crisis has manifested despite clinical access to three approved opioid use disorder medications: the full opioid agonist methadone, the partial opioid agonist buprenorphine, and the opioid antagonist naltrexone. Although current opioid use disorder medications are underutilized, the ongoing opioid crisis has also identified the need for basic research to develop both safer and more effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 90 publications
0
13
0
Order By: Relevance
“… 8 , 9 Vaccines against fentanyl or other opioids, a proposed alternative or adjunct therapy for OUD, operate through production of target-specific polyclonal antibodies, which sequester drug in the serum and reduce brain exposure to the compound of interest. Such vaccines, which consist of an opioid-based hapten conjugated to an immunogenic carrier protein, have shown substantial preclinical efficacy as a strategy to combat OUD and drug-related overdose (reviewed in refs ( 10 and 11 )). A vaccine targeting oxycodone is currently being investigated in subjects with OUD in Phase I clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 Vaccines against fentanyl or other opioids, a proposed alternative or adjunct therapy for OUD, operate through production of target-specific polyclonal antibodies, which sequester drug in the serum and reduce brain exposure to the compound of interest. Such vaccines, which consist of an opioid-based hapten conjugated to an immunogenic carrier protein, have shown substantial preclinical efficacy as a strategy to combat OUD and drug-related overdose (reviewed in refs ( 10 and 11 )). A vaccine targeting oxycodone is currently being investigated in subjects with OUD in Phase I clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Kirby and co-workers have observed similar ring opened side-products when attempting hydrogenation of 4 . 25 This issue was circumvented by first protecting the C6 position as the ketal followed by cleavage of the N–O bond and removal of the Troc group with zinc dust. Hydrolysis of the ketal group after reduction was accomplished utilizing concentrated HCl, affording 7 in 47% over three steps.…”
Section: Resultsmentioning
confidence: 99%
“…3,11,18 More recent works have shown that linker sites at C3 and C6 also yield antibodies selective to target drugs that translate to protection against heroin-induced physiological effects. 3,8,17 With a few on-going efforts to translate experimental opioid vaccines to humans, 25 there is a need to study many variants of a given hapten to fully understand how the molecular scaffold ultimately impacts the selectivity of the induced antibodies, which in turn dictate the vaccine efficacy in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that clinical trial results have only been reported for vaccines against nicotine and cocaine addictions, with the vaccines demonstrating efficacy only in a subset of patients that were able to achieve high neutralizing antibody titers ( 153 , 183 186 ). The recent vaccine developments to ameliorate drug abuse have been reviewed more extensively elsewhere ( 153 , 160 , 187 ).…”
Section: Non-viral Vaccine Systems To Address Ongoing Challenges Of Vmentioning
confidence: 99%